Peritoneal Membrane Injury and Peritoneal Dialysis. (2nd November 2014) - Chugh, Shaan; Chaudhry, Sultan; Ryan, Timothy; Margetts, Peter J.
Abstract : For patients with chronic renal failure, peritoneal dialysis (PD) is a common, life sustaining form of renal replacement therapy that is used worldwide. Exposure to nonbiocompatible dialysate, inflammation, and uremia induces longitudinal changes in the peritoneal membrane. Application of molecular biology techniques has led to advances in our understanding of the mechanism of injury of the peritoneal membrane. This understanding will allow for the development of strategies to preserve the peritoneal membrane structure and function. This may decrease the occurrence of PD technique failure and improve patient outcomes of morbidity and mortality.